Personalised care in maternity. (2nd August 2021) - Winfield, Sarah; Booker, Maria
Abstract : Although COVID-19 has placed immense pressure on healthcare professionals, Dr Sarah Winfield and Maria Booker still believe personalised care is the utmost of importance in maternity services